(3eMGSHI GdJcGdja GdUfGYjI (B/s - (3GdCNQS, YGWas; (3EjeGf Gdgfjfj hBNQhfs ((3YeGf(B: s (3OGQ GdHQcI(B, s, 2001)
(3ebOeI aj eMGSHI GdJcGdja, fXGe GdJcGdja, CfhGY GdJcGdja, YfGUQ GdJcGdja, bhGFe GdCYeGd, fXGe JcGdja ChGeQ GdJTZjd, fXGe JcGdja eQGMd GdJTZjd, fXQjGJ GdJcGdjas
(3GdeQGLY U(B.264s
Keywords: (3eMGSHI GdJcGdjas